Emergence of a novel SARS-CoV-2 Pango lineage B.1.1.526 in West Bengal, India. Issue 1 (January 2022) - Sarkar, Rakesh; Saha, Ritubrita; Mallick, Pratik; Sharma, Ranjana; Kaur, Amandeep; Dutta, Shanta; Chawla-Sarkar, Mamta
Abstract: Background: Since its inception in late 2019, SARS-CoV-2 has been evolving continuously by procuring mutations, leading to emergence of numerous variants, causing second wave of pandemic in many countries including India in 2021. To control this pandemic continuous mutational surveillance and genomic epidemiology of circulating strains is very important to unveil the emergence of the novel variants and also monitor the evolution of existing variants. Methods: SARS-CoV-2 sequences were retrieved from GISAID database. Sequence alignment was performed with MAFT version 7. Phylogenetic tree was constructed by using MEGA (version X) and UShER. Results: In this study, we reported the emergence of a novel variant of SARS-CoV-2, named B.1.1.526, in India. This novel variant encompasses 129 SARS-CoV-2 strains which are characterized by the presence of 11 coexisting mutations including D614G, P681H, and V1230L in S glycoprotein. Out of these 129 sequences, 27 sequences also harbored E484K mutation in S glycoprotein. Phylogenetic analysis revealed strains of this novel variant emerged from the GR clade and formed a new cluster. Geographical distribution showed, out of 129 sequences, 126 were found in seven different states of India. Rest 3 sequences were observed in USA. Temporal analysis revealed this novel variant was first collected from Kolkata district of West Bengal, India. Conclusions: The D614G, P618H and E484K mutations have previously been reported to favor increased transmissibility, enhanced infectivity, and immune invasion, respectively. The transmembrane domain (TM) of S2 subunit anchors S glycoprotein to the virus envelope. The V1230L mutation, present within the TM domain of S glycoprotein, might strengthen the interaction of S glycoprotein with the viral envelope and increase S glycoprotein deposition to the virion, resulting in more infectious virion. Therefore, the new variant having D614G, P618H, V1230L, and E484K may have higher infectivity, transmissibility, and immune invasion characteristics, and thus need to be monitored closely.